Pengaruh kecerdasan emosional, literasi matematis, dan self-efficacy terhadap prestasi belajar matematika - A Rizal Heru Cahya; Cecep AHF Santosa; Anwar Mutaqin (Universitas Sultan Ageng Tirtayasa, 2022)
Abstract: Emotional intelligence as a spectrum of skills, abilities, and non-cognitive competencies affects the ability of learners to cope with environmental demands and pressures. Self-efficacy is a person's belief about his ability to organize and decide certain actions needed to obtain certain results, and mathematical literacy is the ability used in solving mathematical problems related to everyday life. This study uses a survey-type quantitative approach with a population of 3,737 all State MTs students in Serang Regency. The sampling technique used was area random sampling and 380 respondents were selected. Data analysis techniques include outer and inner models as well as bootstrapping. The results showed that there was a positive and significant effect of emotional intelligence on learning achievement in mathematics, there was a positive and significant effect of emotional intelligence on self-efficacy, there was a positive and significant effect of emotional intelligence on mathematical literacy, there was a positive and significant effect of self-efficacy on learning achievement. mathematics, there is a positive and significant influence of mathematical literacy on learning achievement in mathematics, there is a positive and significant influence on emotional intelligence indirectly through self-efficacy on learning achievement in mathematics, and there is a positive and significant influence on emotional intelligence indirectly through mathematical literacy on learning achievement mathematics.